(untitled) (One Health & Risk Management, 2021)
Introduction. In Romania, National Authority for Veterinary Health and Food Safety (NAVHFS) is the institution that coordinates all the activities focused on ensuring food safety by identifying the risky products and eliminating these risks. Material and methods. The purpose of the research was to analyze the way in which the online media communicates the food incidents identified by The National Authority for Veterinary Health and Food Safety. Starting from the list of products that reappeared on the market in 2019 (available list on the website NAVHFS), I evaluated the way in which media communicates about alerts regarding the reappearance of some products infected with Listeria Monocytogenes, Salmonella or that contained unknown substances/unidentified objects. The methodology of the research included the content analysis of the articles identified in the online media. In order to identify the articles, I used key words (food alert, Listeria infections alert, Salmonella infections alert) which I introduced in Google Chrome. The analyzed corpus was of N=119 articles selected according to the mentioned criteria and published in the period January 1st, 2019 – January 1st, 2020. The analysis grid was structured in such way as to allow the identification of some information regarding: the media type, time period, information regarding symptoms, information regarding health consequences, categories of risk population, presence/absence of recommendations regarding necessary measures for protecting the consumer, categories of people who communicate about alerts. The information was analyzed with the help of SPSS 22.2. Results. More than half of the alerts issued by NAVHFS were given for salmon (8 out of 14 alerts). Only two alerts were given for chicken or pork. However, the articles from the online media inform the population to a greater extent about the alerts given for the chicken, pork or beef products (59 articles out of 119). The articles include information about withdrawn products or name the shop chain that sells the products, but they do not present information about health consequences or measures which need to be taken by the population in order to protect their health or in order to be given a refund. Only 14.2% contain information about the diseases caused by consuming such infected products. Almost half of the articles (47%) include information regarding the consequences of consuming spoiled/infected products. Approximately one third of the articles mentions risk groups, i.e. the people who are exposed to the highest risks if they consume Listeria or Salmonella infected products or products that contain many substances that cause allergies. Two out of five articles contain recommendations for the population. Conclusions. The way in which the online media from Romania present the food alerts is different from the way in which traditional media or social media from other countries cover this subject. In Romania journalists include only two topics (scientific and economic topic), while the article from the international media covers four topics (scientific, economic, political and social – Shan et al 2014).